Building corporate social responsibility into strategy - Galbreath, Jeremy (Emerald Group Publishing Limited, 2009)
Purpose: To explore how corporate social responsibility (CSR) can be effectively built into firm strategy. Design/methodology/approach: By drawing upon classics work in the field, this paper first offers conceptual discussion and then systematically develops a means of incorporating CSR into strategy. Findings: Common approaches to CSR, such as PR campaigns, codes of ethics and triple bottom line reports are far to removed from strategy. To counter common and generally non-strategic approaches, a framework is offered which demonstrates that CSR can be linked integrally with strategy, and highlights an approach to consider CSR across six dimensions of firm strategy. Practical implications: Firms do not have to respond reactively towards CSR nor do they have to struggle with understanding the strategic implications of CSR. As this paper demonstrates, examining CSR in the context of firm strategy is both possible and increasingly necessary to developing competitive advantage in the current environment. Originality/value: The value of the paper rests in the treatment of CSR as an issue that is strategic, rather than one that is problematic or potentially a threat. By doing so, firms are offered a means to take a much more proactive approach to CSR than previously discussed.